Japanese business concepts you should know - Parissa Haghirian (Tokyo : [Publishers name not idntified], 2020)
This book gives you an in-depth look at the most famous Japanese management practices and how Japanese corporations utilize them. It examines all aspects of Japanese management and explains the most famous Japanese business concepts such as kaizen, kanban, just-in-time and lifetime employment. It covers all aspects of modern Japanese management and helps international managers understand these successful management practices.
Keywords: Business; Japan